2008
DOI: 10.1073/pnas.0708110105
|View full text |Cite
|
Sign up to set email alerts
|

Role for lysosomal enzyme β-hexosaminidase in the control of mycobacteria infection

Abstract: The pathogenic mycobacteria that cause tuberculosis (TB) and TB-like diseases in humans and animals elude sterilizing immunity by residing within an intracellular niche in host macrophages, where they are protected from microbicidal attack. Recent studies have emphasized microbial mechanisms for evasion of host defense; less is known about mycobactericidal mechanisms that remain intact during initial infection. To better understand macrophage mechanisms for restricting mycobacteria growth, we examined Mycobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 35 publications
6
69
0
Order By: Relevance
“…The effect of FUCA2 on H. pylori was examined by 2 studies: RNA interference-mediated depletion of FUCA2 and treatment of H. pylori-infected cells with FNJ, both of which effectively prevented adherence of H. pylori to host cells The aforementioned host defense mechanism to exploit ␣-Lfucosidase for removal of L-fucose residues was not unexpected. ␤-Hexosaminidase, for instance, was characterized as a peptidoglycan hydrolase that exerts its mycobactericidal effect at the macrophage plasma membrane when secretion from host lysosomes is induced by mycobacteria (32). Moreover, our findings indicate that H. pylori adhesion to host cells is related to the presence of FUCA2.…”
Section: Discussionmentioning
confidence: 48%
“…The effect of FUCA2 on H. pylori was examined by 2 studies: RNA interference-mediated depletion of FUCA2 and treatment of H. pylori-infected cells with FNJ, both of which effectively prevented adherence of H. pylori to host cells The aforementioned host defense mechanism to exploit ␣-Lfucosidase for removal of L-fucose residues was not unexpected. ␤-Hexosaminidase, for instance, was characterized as a peptidoglycan hydrolase that exerts its mycobactericidal effect at the macrophage plasma membrane when secretion from host lysosomes is induced by mycobacteria (32). Moreover, our findings indicate that H. pylori adhesion to host cells is related to the presence of FUCA2.…”
Section: Discussionmentioning
confidence: 48%
“…Striker et al (45) suggested that degradation of gonococcal PGN is mediated by b-hexosaminidase released from neutrophil granules. Additionally, Koo et al (46) reported that b-hexosaminidase exerts mycobactericidal activity in the lysosome of macrophages. Bacterial cell wall PGN is a polymer composed of sugars and amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been successfully manipulated for the identification of genes involved in host-pathogen interactions. These pathogens include Listeria monocytogenes (1,2), Chlamydia trachomatis (20), Mycobacterium marinum (1,18,30,48), Francisella tularensis (51,64), and the protozoan parasite Plasmodium gallinaceum (8,53).…”
mentioning
confidence: 99%